Effect of transaction costs on international remittance flows from developed countries: A Sub-Saharan context - Wahito, Isaac (Research of GSB, 2018)
Remittances play a major role both at a household and a macro-level especially in developing countries. They are associated with benefits such as of economic growth and employment opportunities for a country, while at the household level, remittances are a stable source of income in provision of basic needs such as of food, clothing, shelter and education. Remittance costs have been viewed as a major deterrent to higher volumes of remittance inflows to a country and tend to encourage the use of the cheaper informal channels, which have adverse consequences. This study investigates the drivers of remittance transaction costs and the subsequent effect of transaction costs on remittance flows using bilateral data between several countries in Sub-Saharan Africa and the United Kingdom over the period 2011 to 2014. Remittance costs are measured as a percentage of the amount remitted. Using multivariate generalised least squares analysis of panel data, this study tested the first hypothesis that financial development, banking concentration and financial risk of a migrant's home country influence transaction costs. Secondly, the study tested the hypothesis that transaction costs have a negative relationship with remittance inflows into the countries. The specific effect of transaction costs on remittance flows is investigated alongside other variables which have been identified to influence remittance flows. These include; the stock of migrants in the host country and host and home country income levels proxied by gross domestic product per capita. The results of random effects estimations show that financial development and bank concentration have a positive and statistically significant relationship with transaction costs. That is, a higher level of financial development does not necessarily lower transaction costs but a high banking concentration, which infers lower competition in the banking sector, drives remittance costs up. On the effect of transaction costs on remittance flows into the countries in sub-Saharan Africa, the study found a negative and significant relationship. That is, a higher cost in remitting funds via formal channels reduces the remittance flows and as such, it thus increases the probability of the use of informal channels. The stock of migrants is also found to have a positive and statistically significant effect on remittances, meaning that a higher number of migrants in a developed country leads to higher volumes of remittances to the migrants' home countries. The proxies for incomes were found to be insignificant. The implications of the significance of remittance costs are noteworthy as they add evidence on the need to cut remittance costs by formal channels significantly to three percent of the total amount remitted by global development institutions.